KRITIK SOSIAL DALAM RUANG PUBLIK: STUDI KASUS TAYANGAN ACARA LAPOR PAK! DI TRANS 7 - Abdul Syakur, Hilmy (Icon: Islamic Communication and Contemporary Media Studies, 2025)
Mass media which initially provided various kinds of information now also play a role as a public sphere to provide criticism, ideas and concepts. One of them is the Lapor Pak! broadcast owned by the mass media Trans 7. Using Zulkifli Hasan roasting episode. The focus of this study: 1) To find out how the Lapor Pak! Trans 7 episode "Pedas! Kiky Roasting Zulkifli Hasan" program as a public sphere displays messages of social criticism. 2) To find out the critical discourse analysis of the Lapor Pak! Trans 7 episode "Pedas! Kiky Roasting Zulkifli Hasan" program as a public opinion. In the research, using qualitative descriptive research techniques with critical discourse analysis by Teun A. Van Dijk. In descriptive research, it is more about various kinds of series of words, images, or documents so that without using data in the form of numbers. The conclusion is that: 1) Lapor Pak! in this case uses the scene roasting executed by Kiky Saputri to carry out social criticism in the public sphere. 2) Social criticism carried out by Kiky Saputri is intended to control social and political matters that are considered deviant by society.